2013
DOI: 10.1002/mabi.201370025
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Biosci. 8/2013

Abstract: Front Cover: http://doi.wiley.com/10.1002/mren.201200416, A. Ferrari, D. Poulikakos, and coworkers present a novel approach to fabricating optically accessible, 3D integrated platforms, simulating the cell microenvironment during interstitial migration. The platforms consist of free‐form, 3D micropores printed on demand on basal scaffolds with microgratings, and are employed to monitor cancer cell migration using highresolution optical microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The drug-likeness properties were evaluated by Pfizer's rule (also called as Lipinski's rule), wherein it states that those candidates that have values of log P ≤ 5, HBD ≤ 5, HBA ≤ 10, MW ≤ 500, TPSA (<140), and AMR (40–130), are considered to have passed the drug-likeness analysis [ 37 ]. These above parameters influence the bioavailability, absorption, receptor-drug interactions, metabolism and their toxicity [ 56 ]. The size of the molecule is also an important factor for drug candidates and it is useful for membrane transportation [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The drug-likeness properties were evaluated by Pfizer's rule (also called as Lipinski's rule), wherein it states that those candidates that have values of log P ≤ 5, HBD ≤ 5, HBA ≤ 10, MW ≤ 500, TPSA (<140), and AMR (40–130), are considered to have passed the drug-likeness analysis [ 37 ]. These above parameters influence the bioavailability, absorption, receptor-drug interactions, metabolism and their toxicity [ 56 ]. The size of the molecule is also an important factor for drug candidates and it is useful for membrane transportation [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The normalized H data should be treated with corresponding care, although we tried to select a value that is most representative of the available literature. References for literature data: EHDP, [42] LAEPD, [43] LIFT (ink), [47,78,79] MCED, [26,51] FluidFM, [54] EHD-RP, [57] FEBID. [22,[59][60][61][62] *: Pt nanoparticles embedded in a carbonaceous matrix.…”
Section: Limitations Of the Study And Validity And General Applicability Of The Resultsmentioning
confidence: 99%
“…), [41] 6 (ann.) [42] 0. LAEPD -Laser-assisted electrophoretic deposition of nanoparticles [43] Au 1.5 (ad.)…”
Section: Overview Of Included Am Methods and Samplesmentioning
confidence: 99%
“…15,16 It has been used to deposit inks containing colloidal nanomaterials, 15,16 polymers 17,18 and biomaterials 19 with femto-to attoliter volumes and has been applied to the field of flexible electronics [20][21][22][23] and biotechnology. 24,25 In addition to using EHD printing to write functional micro-and nanostructures, it was recently shown that the EHD nanodripping mode is able to generate and sustain ultra-small droplets under an open atmosphere on non-wetting surfaces. 26 In this work, we combine the open atmosphere printing capability of EHD nanodripping with a novel ink chemistry and the generation of sessile droplets acting as attoliter reactors to advance the status of site-specific particle deposition to the level of printing single nanoparticles.…”
Section: Introductionmentioning
confidence: 99%